Estimation of ultrashort laser pulse penetration depth into plasma at multiphoton collisional absorption - Zaitsev, D.V. (Вопросы атомной науки и техники, 2000)
The interaction of ultrashort laser pulses with plasma is studied, where the pulse is considered as a photon flux and the plasma is presented by an ensemble of free electrons absorbing photons due to backstopping. The penetration depth is estimated for powerful ultrashort laser pulses at multiphoton collisional absorption.